Analysis of CO2 emissions resulting from electricity sector in Turkey by using Boğaziçi University Energy Modeling System (BUEMS) modeling framework - Kalkan, Emre. (Thesis (Ph.D.) - Bogazici University. Institute of Environmental Sciences, 2022., 2022)
Due to factors such as industrialization, increase in population and economic growth electricity demand has shown a significant increase at global scale. This increase has put forward discussions concerning electricity supply security, source diversification and clean electricity generation. Fossil based electricity generation featured the transition to clean generation in this sector. Particularly, towards the goal of the Paris Agreement, policy developments have gained momentum to reach carbon neutral electricity sector by 2050. These developments have been closely monitored by Turkey. The purpose of this thesis is to evaluate long-term results of the CO2 emissions resulting from electricity sector in Turkey by using BUEMS model in line with latest available data and updated policy papers. Total electricity installed capacity, generation portfolio and increase in electricity demand were investigated. In the context of the thesis, a Base scenario was established. The response of the electricity sector under carbon tax and emission restrictions and their effect to CO2 emissions were analyzed. The results of the study showed that tax and emission targets played an important role for CO2 emission reduction. In Base Scenario, Total CO2 emissions exceeded 1,000 Million tons and electricity sector’s contribution was almost 680 Million tons in the year 2057. Among all scenarios the highest decrease was obtained under Peak Emission Scenario. Total emissions reduced to 705 Million tons and emissions from electricity sector decreased by 61% compared to Base Scenario and fell to 244 Million tons in 2057 by means of renewables and nuclear penetration.
Keywords: Boğaziçi University Energy Modeling System (BUEMS); Energy policy -- Turkey.; Carbon dioxide mitigation.